Food and temperature stressors have opposing effects in determining flexible migration decisions in brown trout (Salmo trutta). (27th February 2020) - Archer, Louise C.; Hutton, Stephen A.; Harman, Luke; McCormick, Stephen D.; O'Grady, Michael N.; Kerry, Joseph P.; Poole, W. Russell; Gargan, Patrick; McGinnity, Philip; Reed, Thomas E.
Abstract: With rapid global change, organisms in natural systems are exposed to a multitude of stressors that likely co‐occur, with uncertain impacts. We explored individual and cumulative effects of co‐occurring environmental stressors on the striking, yet poorly understood, phenomenon of facultative migration. We reared offspring of a brown trout population that naturally demonstrates facultative anadromy (sea migration), under different environmental stressor treatments and measured life history responses in terms of migratory tactics and freshwater maturation rates. Juvenile fish were exposed to reduced food availability, temperatures elevated to 1.8°C above natural conditions or both treatments in combination over 18 months of experimental tank rearing. When considered in isolation, reduced food had negative effects on the size, mass and condition of fish across the experiment. We detected variable effects of warm temperatures (negative effects on size and mass, but positive effect on lipids). When combined with food restriction, temperature effects on these traits were less pronounced, implying antagonistic stressor effects on morphological traits. Stressors combined additively, but had opposing effects on life history tactics: migration increased and maturation rates decreased under low food conditions, whereas the opposite occurred in the warm temperature treatment. Not all fish had expressed maturation or migration tactics by the end of the study, and the frequency of these 'unassigned' fish was higher in food deprivation treatments, but lower in warm treatments. Fish showing migration tactics were smaller and in poorer condition than fish showing maturation tactics, but were similar in size to unassigned fish. We further detected effects of food restriction on hypo‐osmoregulatory function of migrants that may influence the fitness benefits of the migratory tactic at sea. We also highlight that responses to multiple stressors may vary depending on the response considered. Collectively, our results indicate contrasting effects of environmental stressors on life history trajectories in a facultatively migratory species. Abstract : Many species show the ability to flexibly express migration, whereby individuals can vary in migratory and residency tactics. We tested how co‐occurring environmental stressors influenced migratory decisions in brown trout. While food and temperature stressors negatively affected some traits such as size, the effects were less than expected when stressors were combined. Moreover, reduced food increased migration, but warm temperatures decreased migration. Our study indicates how aspects of global change might affect life history diversity and traits related to performance.